The Relationship Between Occupational Stress and Turnover Intention Among Emergency Physicians: A Mediation Analysis - Jiang, Nan; Zhang, Hongling; Tan, Zhen; Gong, Yanhong; Tian, Mengge; Wu, Yafei; Zhang, Jiali; Wang, Jing; Chen, Zhenyuan; Wu, Jianxiong; Lv, Chuanzhu; Zhou, Xuan; et al. (Frontiers in Public Health, 2022)
Background There is evidence that occupational stress is a risk factor for turnover intentions. However, the structural relationship between occupational stress and turnover intention among emergency physicians has rarely been studied. This study aimed to examine the pathways of occupational stress on turnover intention through job satisfaction and depressive symptoms among emergency physicians in China. Methods A cross-sectional study was conducted in China from July 2018 to August 2018. Data were collected using a structured questionnaire that included demographic characteristics, occupational stress, job satisfaction, depressive symptoms, and turnover intention. Hierarchical linear regression was performed to explore the related factors of turnover intention. Structural equation modeling was used to examine the pathways from occupational stress to turnover intention. Results A total of 10,457 emergency physicians completed the questionnaire. The score of turnover intention was 11.34 (SD = 3.25), and the average item score of turnover intention was 2.84 (SD = 0.81). In structural equation modeling, the occupational stress not only had a direct effect on turnover intention (standardized direct effect = 0.311, bias-corrected 95% confidence interval [0.261, 0.361], P < 0.001), but also had an indirect effect through job satisfaction and depressive symptoms (standardized indirect effect = 0.448, bias-corrected 95% confidence interval [0.412, 0.484], P < 0.001). However, the effect of depressive symptoms on turnover intention was weak (standardized coefficient [β] = 0.08, P < 0.001). Conclusions Job satisfaction partially mediated the relationship between occupational stress and turnover intention. However, due to the weak effect of depressive symptoms on turnover intention, the mediating role of depressive symptoms between occupational and turnover intention had little practical value. It is recommended that hospital administrators prioritize increasing job satisfaction of emergency physicians to reduce the impact of occupational stress on their turnover intention.